Development and Impact of the Use of Slang on Instagram Social Media on Teenagers and Society: Case Study of Indonesian in the Digital Era: Development and Impact of the Use of Slang on Instagram Social Media on Teenagers and Society: Case Study of Indonesian in the Digital Era - Saputra, Renda Sandi; Salih, Yasir (International Journal of Linguistics, Communication, and Broadcasting, 2023)
The use of slang in Instagram social media among teenagers has become a significant phenomenon. This article investigates the factors that influence the use of slang and its impact on adolescents. The results of the study show that the development of the times, the influence of the internet and electronic media have contributed to the spread of slang. The impact of using slang includes expression of positive identity and more intimate communication, but also includes the potential for decreased interest in good and correct Indonesian, ambiguity in official vocabulary, and negative use. In this digital era, it is important to understand the consequences of using slang on social media and how education and awareness about proper language can help young people overcome this challenge.